2021
DOI: 10.1099/jmm.0.001318
|View full text |Cite
|
Sign up to set email alerts
|

On the emergence, spread and resistance of Candida auris: host, pathogen and environmental tipping points

Abstract: Over a decade ago, a multidrug-resistant nosocomial fungus Candida auris emerged worldwide and has since become a significant challenge for clinicians and microbiologists across the globe. A resilient pathogen, C. auris survives harsh disinfectants, desiccation and high-saline environments. It readily colonizes the inanimate environment, susceptible patients and causes invasive infections that exact a high toll. Prone to misidentification by conventional microbiology techniques, C. auris rapidly acquires multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 138 publications
(280 reference statements)
1
106
0
6
Order By: Relevance
“…и Пакистане (штамм 2008 г.) [3,4]. Эти данные свидетельствуют о существовании вида C. auris до 2009 г. Однако незна чительное количество выявленных при пересмотре кол лекций клинических штаммов C. auris говорит о крайне низкой частоте вызываемых им инфекций в тот период.…”
Section: распространение C Auris в евразииunclassified
See 1 more Smart Citation
“…и Пакистане (штамм 2008 г.) [3,4]. Эти данные свидетельствуют о существовании вида C. auris до 2009 г. Однако незна чительное количество выявленных при пересмотре кол лекций клинических штаммов C. auris говорит о крайне низкой частоте вызываемых им инфекций в тот период.…”
Section: распространение C Auris в евразииunclassified
“…Полногеномное секвенирование C. auris, выделен ных в различных странах, выявило 4 основные попу ляции, в которых изоляты кластеризуются в зависимо сти от предполагаемого региона происхождения [3,4]. КМАХ .…”
Section: Introductionunclassified
“…The most worrisome aspects associated with infection caused by C. auris can be summarized in three levels: High rate of antifungal drug resistance [ 9 ], mode and pace of its easy transmission among healthcare workers and patients in hospitals, and misidentification. This last level is related to difficulties in a correct identification of C. auris strains, which are commonly misidentified as other phylogenetically-related pathogens, but also due to inadequacies of common diagnostic tools to precise identification of C. auris in many countries that result in misidentification and incorrect therapy, which lead to the acquisition of multiple genetic determinants that confer multidrug resistance [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it rapidly colonizes abiotic surfaces, immunosuppressed individuals, and causes invasive infections that exact a high toll [ 7 , 14 , 15 , 16 , 17 , 18 , 19 ]. Studies have demonstrated that the Hog1-related stress-activated protein kinase (SAPK) signaling pathway has a central role in the C. auris reaction to osmotic stress, and it is a crucial virulence factor in several human fungi [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, even as knowledge about C. auris grows, notable gaps remain in the understanding of Candida auris emergence, spread, and resistance [9]. Especially from countries such as Qatar, Jordan, and Egypt [10].…”
Section: Introductionmentioning
confidence: 99%